2006
DOI: 10.1038/sj.onc.1210157
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of apoptosis in Rb-deficient embryos via Abl knockout

Abstract: The retinoblastoma protein RB regulates cell proliferation, differentiation and apoptosis. Homozygous knockout of Rb in mice causes embryonic lethality owing to placental defects that result in excessive apoptosis. RB binds to a number of cellular proteins including the nuclear Abl protein and inhibits its tyrosine kinase activity. Ex vivo experiments have shown that genotoxic or inflammatory stress can activate Abl kinase to stimulate apoptosis. Employing the Rb-null embryos as an in vivo model of apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…31 TUNEL assay was performed as described by Borges and co-workers. 47 Ki-67 antibody used was purchased from BD Pharmingen, San Diego, CA, USA. All cell nuclei were stained with 4′,6-Diamidino-2-phenylindole (DAPI, blue).…”
Section: Figurementioning
confidence: 99%
“…31 TUNEL assay was performed as described by Borges and co-workers. 47 Ki-67 antibody used was purchased from BD Pharmingen, San Diego, CA, USA. All cell nuclei were stained with 4′,6-Diamidino-2-phenylindole (DAPI, blue).…”
Section: Figurementioning
confidence: 99%
“…Several organs have been employed as in vivo models of IR-induced apoptosis: the gastro-intestinal (GI) tract, the thymus, the developing liver and the developing CNS [47][48][49][50]. Among those, the developing CNS has so far been the most investigated, and thus the focus of this discussion.…”
Section: In Vivo Cell Death Response To Irmentioning
confidence: 99%
“…In the context of Rb-deficiency, reduced levels of c-Abl and activation of various apoptotic factors were observed. The C-terminal domain of the Rb protein binds to the kinase domain of c-Abl and inhibits its pro-apoptotic catalytic activity [22], [24], [26], [28], indicating a negative feedback loop between reduced Rb-levels and c-Abl expression. It has been demonstrated that Rb-knockout embryos exhibited inappropriate cell cycle entry and massive apoptosis in nervous system, lens, liver and muscles [64].…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that Rb-knockout embryos exhibited inappropriate cell cycle entry and massive apoptosis in nervous system, lens, liver and muscles [64]. According to Borges et al, in Rb-null mice embryos, the knockout of either one or two abl alleles can reduce CNS and liver apoptosis in early embryos suggesting that in Rb −/− genetic background, the pro-apoptotic activity of c-Abl may be enhanced due to the loss of Rb control of the nuclear Abl kinase activity [24]. Other studies have demonstrated that cultured thymocytes derived from rb −/−/ abl −/− embryos showed a reduced apoptotic response to TNF-α [23] and to ionizing radiation in ex vivo cultures [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation